Who got what, then and now? A fifty year overview from the Global Consumption and Income Project - Arjun Jayadev; Rahul Lahoti; Sanjay G. Reddy (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
Using newly comprehensive data and tools from the Global Consumption and Income Project or CGIP, covering most of the world and five decades, we present a portrait of the changing global distribution of consumption and income and discuss its implications for our understanding of inequality, poverty, inclusivity of growth and development, world economic welfare, and the emergence of a global "middle class". We show how regional distributions of income and consumption have evolved very differently over time. We also undertake sensitivity analysis to quantify the impact of various choices made in database construction and analysis. We find that levels of consumption and income have increased across the distribution, that the global distribution has become more relatively equal due to falling inter-country relative inequality, and that by some measures global poverty has declined greatly but by others it has hardly declined at all, even over the fifty years. The global middle class has grown markedly in certain countries but only slightly worldwide. Most of the marked changes have occurred after 1990. China's rapid economic growth is by far the most important factor underlying almost all of them, notwithstanding sharply increasing inequalities within the country. Most improvements outside of China are associated with rapid developing country growth after 2000, and are of unknown durability. Country-experiences vary widely; there is for instance some evidence of "inequality convergence" with previously more equal countries becoming less equal over time and the obverse. We provide support for previous findings (e.g. the replacement of the global "twin peaks" by a unimodal distribution) but also arrive at some conclusions that overthrow old "stylized facts" (e.g. that the Sub-Saharan African countries, and not Latin American ones, have the highest levels of inequality in the world, when measured using standardized surveys). The GCIP provides a resource for ongoing analysis, and forecasting, of developments in the world distribution.
Keywords: D30; D31; D60; D63; I30; O10; O15; P50; 330; Global Distribution; Inequality; Poverty; Economic Growth; Welfare